2015
DOI: 10.3892/ijo.2015.3155
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of thalidomide for gemcitabine-resistant bladder cancer

Abstract: Controversial effects of thalidomide for solid malignancies have been reported. In the present study, we evaluate the effects of thalidomide for transitional cell carcinoma (TCC), the most common type of bladder cancer. Thalidomide precipitates were observed when its DMSO solution was added to the culture medium. No precipitation was found when thalidomide was dissolved in 45% γ-cyclodextrin, and this concentration of γ-cyclodextrin elicited slight cytotoxicity on TCC BFTC905 and primary human urothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Although some researchers argued whether securin is necessary for mitosis in certain cells, the fact regarding securin as oncoprotein is indubitable [ 16 18 ]. The high expression level of securin appears in breast cancer, lung cancer, and bladder cancer, and it is widely involved in malignant proliferation, invasion, and angiopoiesis [ 19 21 ]. According to the published data, securin also serves as a tumor-promoter in glioma, and the overexpression of securin in high-grade glioma heraldes the bad prognosis [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some researchers argued whether securin is necessary for mitosis in certain cells, the fact regarding securin as oncoprotein is indubitable [ 16 18 ]. The high expression level of securin appears in breast cancer, lung cancer, and bladder cancer, and it is widely involved in malignant proliferation, invasion, and angiopoiesis [ 19 21 ]. According to the published data, securin also serves as a tumor-promoter in glioma, and the overexpression of securin in high-grade glioma heraldes the bad prognosis [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…30,31 THA has been found to exhibit preventative and therapeutic effects in various cancer species and has been confirmed to be a potent chemosensitizer. 9,32 However, due to the extreme hydrophobicity and degradation characteristics exhibited by this compound in vivo, the use of THA is vastly limited and THA may not be administered via the intravenous route. Furthermore, the poor water solubility of THA limits the delivery characteristics of the drug to the tumor site at an effective concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] So far, worldwide studies on THA intervention in malignant tumors, including hematological malignancy and solid tumors, such as lung cancer, bladder cancer, pancreatic carcinoma, and hepatocellular carcinoma, have been reported. [9][10][11][12][13][14] However, due to several physical properties of THA, including insolubility in water, no parenteral preparation is available and the overall applicability vastly restricted. 15 In recent years, nanotechnology has been developed as an important scientific field that now attracts a significant amount of attention in drug delivery and cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another in vitro study on ovarian cancer also reported that THD was able to inhibit the proliferation of ovarian cancer cells SKOV3 (36), which suggested that THD may have a role in promoting anti-tumor effects by directly inhibiting proliferation. On the other hand, THD was also able to promote the apoptosis of transitional cell carcinoma cells (37).…”
Section: Discussionmentioning
confidence: 99%